Design and development of hall sensors for magnetic microsystems - Takbiri, Nazanin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Nowadays, magnetic sensors are widely used in variety of applications. One of the most common classes of magnetic sensors is Hall e ect based sensors. Improving characteristics of Hall e ect based sensors, such as sensitivity, resolution, power consumption, and chip area has always been a center of attention for many researchers. In this work, a Hall sensor is designed in 0:13 m CMOS technology. Two cross-shaped Hall plates are used to increase sensitivity and to cancel the DC o set output of Hall plates. To provide input current for the Hall plates, a biasing circuit is designed. Using a common mode feedback network, consistency of the input current is ensured. To automatically ignore the process variations, which causes asymmetric output from di erent Hall plate ports, the current spinning method is used. 32 switches are connected to input-output ports of the Hall plates to rotate their connections functionality and compensate the probable defects after fabrication. A digital circuit is designed to generate 4 non-overlapping clock signals to control the switches. In order to increase signal to noise ratio, the signal is converted from current to voltage mode using a capacitor and then ampli ed using two fully di erential ampli ers. The capacitor is discharged every complete cycle to ensure linear functionality. Layouts of di erent blocks used in the project are designed and pre-layout and post-layout simulation results are gathered and presented. Simulation results show sensitivity of 8383 V A:mT and power consumption of 36 W, while using 3 A as input bias current, 1.8 V as supply voltage, and consuming 6259 m2 of chip area.
Keywords: Microelectronics.